Initial indications of polycyclic aromatic hydrocarbon exposure in Saskatchewan common loons - James D. Paruk; Michael Chickering; John N. Mager; Steven C. Wilkie; Richard H.M. Espie (Canadian Science Publishing, 2018)
Mercury (Hg) and polycyclic aromatic hydrocarbons (PAHs) are global pollutants known for their toxicity to wildlife. Because of their trophic position, common loons (Gavia immer (Brünnich 1764)) are excellent indicators of environmental quality. In 2014 and 2015, tissue samples of ten adult common loons (plus one recapture) were obtained in Meadow Lake Provincial Park, Saskatchewan, and assessed for Hg and PAH exposure. Blood and feather levels of these contaminants are indicative of exposure during breeding and in wintering areas, respectively. Compared with an international Hg database, blood Hg levels were low (<1 μg/g). In most loons (90.5%, 10 out of 11), blood PAH concentrations were also low (<10 ng/g), but high (120 ng/g) for one individual (9.5% 1 out of 11). Feather PAH concentrations were high (95.9 ng/g and 250.6 ng/g) in two of the four loons (50%) caught in 2015. These data indicate that loons breeding in Meadow Lake Provincial Park were exposed to low levels of Hg; however, some individuals are being exposed to PAHs in both their breeding and wintering locations. The effect of these environmental pollutants on individual loon fitness is unclear, but because of their extreme toxicity in biological systems we suggest that future monitoring in the surrounding region is warranted.